E-Learning Model And Conventional Learning Model of Literal Reading Course - Pratiwi, Annisa Regina; Kuspiyah , Hastuti Retno; Hardiansyah, Hardiansyah; Haidorizal , Rifkan (ANFA MEDIATAMA, 2023)
This thesis is entitled E-Learning and Conventional Learning of Literal Reading. The aim of this research is to find out whether there is a significant difference between students taught using the E-Learning model and students taught using the Conventional learning model to teach the Literal Reading course in the second semester at the Nurul Huda University. In this research the author used a descriptive-comparative method with a qualitative approach. The E-Learning model makes students more active compared to conventional learning models. In the E-Learning model, lectures only help students learn. In this case, a student spends more time studying alone. However, in the conventional learning model, lecturers must explain the entire course content to students. Therefore, the E-Learning model provides more quality to students than conventional learning models. It can be concluded that the E-Learning model has advantages compared to conventional learning models. Aside from that, e-learning is more affordable, adaptable, and dynamic than traditional learning approaches. Therefore, as compared to traditional learning models, e-learning provides pupils with a higher quality education.